2000
DOI: 10.1210/jcem.85.3.6431
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetogenic Action of Cholecystokinin-8 in Type 2 Diabetes*

Abstract: Cholecystokinin (CCK) is a gut hormone and a neuropeptide that has the capacity to stimulate insulin secretion. As insulin secretion is impaired in type 2 diabetes, we explored whether exogenous administration of this peptide exerts antidiabetogenic action. The C-terminal octapeptide of CCK (CCK-8) was therefore infused i.v. (24 pmol/kg x h) for 90 min in six healthy postmenopausal women and in six postmenopausal women with type 2 diabetes. At 15 min after start of infusion, a meal was served and ingested duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…The lack of any change in CCK concentrations observed in our study remains in agreement with recent reports that CCK does not stimulate insulin secretion under physiologic conditions in humans, but it does so after the administration of pharmacologic amounts. 37,38 Finally, we would like to address some methodological issues. The difference in the mean plasma estradiol levels between transdermal and oral HT groups resulted from the administered dose of estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of any change in CCK concentrations observed in our study remains in agreement with recent reports that CCK does not stimulate insulin secretion under physiologic conditions in humans, but it does so after the administration of pharmacologic amounts. 37,38 Finally, we would like to address some methodological issues. The difference in the mean plasma estradiol levels between transdermal and oral HT groups resulted from the administered dose of estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…In general, in humans, CCK does not fulfil the criteria for being a physiological incretin hormone, i.e. the ability to augment postprandial glucosestimulated insulin secretion (220,221,223). However, in a small study by Ahrén et al (220), CCK8 was infused into six healthy and six type 2 diabetic postmenopausal women during a meal test and it has been demonstrated that CCK8 (in doses that have been shown to increase insulin secretion) did not affect the postprandial secretion of GIP and GLP1.…”
Section: Tgr5-independent Mechanismsmentioning
confidence: 99%
“…However, in a small study by Ahrén et al (220), CCK8 was infused into six healthy and six type 2 diabetic postmenopausal women during a meal test and it has been demonstrated that CCK8 (in doses that have been shown to increase insulin secretion) did not affect the postprandial secretion of GIP and GLP1. Although the majority of studies do not support a role for CCK-induced, postprandial incretin secretion (220,223,224,225,226,227), it should be underlined that in the physiological setting of mixed meal intake, a stimulatory effect of CCK on postprandial GLP1 release may easily be overlooked due to the meal response, which could 'drown' the effect of CCK itself. Furthermore, any response must be seen in the light of potential effects of endogenous CCK in control experiments.…”
Section: Tgr5-independent Mechanismsmentioning
confidence: 99%
“…However, although CCK is released after meal ingestion, it does not seem to work as an incretin in humans, because circulating levels of CCK after meal ingestion are not sufficient to stimulate insulin secretion and, furthermore, CCK receptor antagonism does not inhibit insulin secretion after meal ingestion [47]. Nevertheless, pharmacologic administration of the peptide was recently shown to be antidiabetogenic in subjects with type 2 diabetes by reducing postprandial glycemia [48]. This finding deserves further study.…”
Section: Gip In Diabetesmentioning
confidence: 99%